(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the problem of organization the system of education on the occupied Polish lands. The main directions, peculiarities and results of education police are characterized. Nazi policy in Poland in the sphere of education is analyzed in the period of September 1939 – June 1941.